CERITA BERTEMA MORAL DAN EMPATI REMAJA AWAL - Muhammad Muchlish Hasyim; Muhammad Farid (University of Merdeka Malang, 2012)
Abstract Experimental study examines the moral-themed stories to foster empathy on adolescence. Research subjects 205 early adolescents, 103 adolescents (56 males, 47 females) selected as the experimental group, and 102 (61 male, 41 female) were selected as the control group. Sixteen given moral-themed stories twice a week. Experiments using the One Group Post-test Design. Control is done by banning adolescence on the experimental group discuss, or lend anything to do with the course of the experiment. Reinforcement is done by discussion and question and answer, draw conclusions in the form of wisdom, and benefits in daily life; Any story, story teller lend sheets to adolescence groups of experiments to be read again at home to make it more understandable. After the eighth week end of the experiment, measurements of empathy were taken with the Davis Interpersonal Relativity Index (IRI). Experimental results showed: 1) Empathy fantasy of experimental was higher than the control group; 2) Average of empathy at all aspects no differ between the experimental and the control group; 3) Average of perspective taking empathy on girls was higher than boys; 4) Average on all aspects of empathy did not differ between boys and girls. Themed story can only cultivate the moral character of fantasy empathy. Moral themed stories will make adolescent lost in fictional stories and imagine themselves in the same situation as fictional characters. The findings are discussed in terms of their implications for early adolescent in context. Key words: Themed Strory Moral, Emphaty, Early Adolescence